INTRODUCTION TO THE GEOLOGICAL MAP OF THE NORTH KARAKORUM TERRAIN FROM THE CHAPURSAN VALLEY TO THE SHIMSHAL PASS 1:150.000 SCALE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
These notes introduce a new geological map at 1:150,000 scale of a large part of the Upper Hunza valley (Karakorum, Pakistan). The mapped area includes the Permian to Cretaceous sedimentary cover of the Karakorum, which is located north of the Karakorum Axial Batholith. The mapped sedimentary and intrusive complexes form four major tectonic units, stacked in a very complex system, due to polyphase events, spanning from Cretaceous to Cenozoic. These events are linked to repeated collisions against the Asian margin of the Kohistan Arc during the Cretaceous and of the Indian Plate during the Cenozoic. Beyond the stratigraphic and structural characteristics of the deformed units, our map also considers the general setting of quaternary deposits.
Keywords: Geological map; Karakorum; Pakistan.